Repulsion Loss: Detecting Pedestrians in a Crowd - Wang, Xinlong; Xiao, Tete; Jiang, Yuning; Shao, Shuai; Sun, Jian; Shen, Chunhua (2018 IEEE/CVF Conference on Computer Vision and Pattern Recognition, 2018)
Detecting individual pedestrians in a crowd remains a challenging problem since the pedestrians often gather together and occlude each other in real-world scenarios. In this paper, we first explore how a state-of-the-art pedestrian detector is harmed by crowd occlusion via experimentation, providing insights into the crowd occlusion problem. Then, we propose a novel bounding box regression loss specifically designed for crowd scenes, termed repulsion loss. This loss is driven by two motivations: the attraction by target, and the repulsion by other surrounding objects. The repulsion term prevents the proposal from shifting to surrounding objects thus leading to more crowd-robust localization. Our detector trained by repulsion loss outperforms the state-of-the-art methods with a significant improvement in occlusion cases.